Preferred communication techniques by student-providers and patients during caries management in a teaching practice: a quality improvement study - Franklin Zhang; Juanna J. Xie; Supattriya Chutinan; Christine A. Riedy (BMC Medical Education)
Abstract Background Clear and concise communication between providers and patients is the cornerstone of building trust and delivering effective medical and oral healthcare. The aim of this quality improvement study was to examine patient-provider communication during caries management sessions in an academic dental teaching practice. Methods Questionnaires were administered to student-providers (3rd and 4th years) and patients (age 18+) in the Harvard Dental Center Teaching Practice from July through December 2022. The student-provider questionnaire assessed challenges, adherence, and communication approaches used during caries management. The patient questionnaire focused on patients’ communication preferences, understanding of caries, oral health literacy, and attitudes towards caries management. Descriptive analyses were calculated for both student-provider and patient data, and open-ended student-provider responses were analyzed using a content analysis and organized into themes. Results Questionnaires were completed by 34 student-providers (50% response rate) and a convenience sample of 110 patients. Among student-providers who reported conducting a caries management session, all reported using simple language and 65.6% focused on discussing limited concepts at a time. Patients preferred simple language (54.8%), motivational interviewing (47.1%), and visual aids, such as models and x-rays (40.4%), to better understand concepts. A subset of student-providers (39.3%) reported challenges in effectively communicating and motivating patients to improve oral hygiene habits. Approximately half of the patients (55.2%) felt confident completing dental forms independently. Regarding their understanding of caries, 54.7% of patients responded that tooth decay will always necessitate fillings and 43.6% of patients responded that they will know when they have tooth decay. Conclusions These findings highlight the importance of interpersonal communication skill training in dental education to facilitate productive provider-patient communication, particularly in the context of caries risk assessment and management.